2020
DOI: 10.1049/mnl.2019.0272
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic hyperthermia behaviour of Co and reduced GO nanocomposites

Abstract: Co-precipitation of CoCl 2 .6H 2 O with graphene oxide (GO) and heating at 400°C for 4 h under hydrogen resulted in the construction of cobalt/ reduced GO (Co/rGO) nanocomposite utilisable in magnetic thermal therapy. Field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, vibrating sample magnetometry, thermogravimetric analysis/derivative thermogravimetry, and X-ray diffraction methods characterised the samples. Time-temperature curves of the samples c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…After 5 min, Co-rGO reached 57 °C, while Co and GOn only raised their temperatures to 48 °C and 39.5 °C, respectively. [44] Alkhayal et al [45] reported rGOn conjugated with Fe 3 O 4 and PEG for cancer MHT. rGOn-Fe 3 O 4 -PEG heating by stimulation with an AMF of 200 A was evaluated at a concentration of 1.6 mg mL −1 using PBS and DMSO as dispersing media.…”
Section: Graphene-based Materials (Gbm)mentioning
confidence: 99%
See 4 more Smart Citations
“…After 5 min, Co-rGO reached 57 °C, while Co and GOn only raised their temperatures to 48 °C and 39.5 °C, respectively. [44] Alkhayal et al [45] reported rGOn conjugated with Fe 3 O 4 and PEG for cancer MHT. rGOn-Fe 3 O 4 -PEG heating by stimulation with an AMF of 200 A was evaluated at a concentration of 1.6 mg mL −1 using PBS and DMSO as dispersing media.…”
Section: Graphene-based Materials (Gbm)mentioning
confidence: 99%
“…Kakavand et al. [ 44 ] produced rGOn modified with Co as a potential MHT agent. Co‐rGOn temperature increase after exposure to a 1500 W magnetic field with 24.8 kA/m intensity and a frequency of 150 kHz, was evaluated at a concentration of 100 µg mL −1 .…”
Section: D Nanomaterialsmentioning
confidence: 99%
See 3 more Smart Citations